2010
DOI: 10.2319/022210-110.1
|View full text |Cite
|
Sign up to set email alerts
|

Chin cup effects using two different force magnitudes in the management of Class III malocclusions

Abstract: The use of a chin cup improved the maxillomandibular base relationship in growing patients with Class III malocclusion but with little skeletal effect. The utilization of either force had the same effects, except that the higher force had a more pronounced effect in reduction of ramus height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 25 publications
(48 reference statements)
3
50
0
12
Order By: Relevance
“…This observation is in agreement with the studies reported by Tuncer et al 11 and Altuğ et al 16 However, other studies failed to show any similar changes. 3,10,17 This study showed significant reduction of all mandibular skeletal variables (Ar-Go, Co-Go, Co-Gn, and SNB) except Go-Gn and this agrees with earlier studies. 3,10,11,17 This reduction could be explained as the result of the force of CC, which is applied directly to the mandible for trying to restrict its horizontal growth and convert it to some extent into vertical growth.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This observation is in agreement with the studies reported by Tuncer et al 11 and Altuğ et al 16 However, other studies failed to show any similar changes. 3,10,17 This study showed significant reduction of all mandibular skeletal variables (Ar-Go, Co-Go, Co-Gn, and SNB) except Go-Gn and this agrees with earlier studies. 3,10,11,17 This reduction could be explained as the result of the force of CC, which is applied directly to the mandible for trying to restrict its horizontal growth and convert it to some extent into vertical growth.…”
Section: Discussionsupporting
confidence: 81%
“…3,10,17 This study showed significant reduction of all mandibular skeletal variables (Ar-Go, Co-Go, Co-Gn, and SNB) except Go-Gn and this agrees with earlier studies. 3,10,11,17 This reduction could be explained as the result of the force of CC, which is applied directly to the mandible for trying to restrict its horizontal growth and convert it to some extent into vertical growth. 18 However, a study by Deguchi and McNamara 14 observed no significant changes by CC therapy in class III patients.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations